Pancreatic Expression of Immunoglobulin G in Human Pancreatic Cancer and Associated Diabetes. Issue 8 (November 2015) - Wan, Xia; Lei, Yu; Li, Zhuo; Wang, Juping; Chen, Zhengshan; McNutt, Michael; Lin, Danyi; Zhao, Conghui; Jiang, Chunfan; Li, Jing; Pu, Qinxue; Su, Min; et al.
Abstract : Objectives: The prognosis of pancreatic cancer (PC) is poor and the pathogenesis of PC-associated diabetes is unknown. We investigated the possible expression of immunoglobulin G (IgG) in human pancreatic carcinomas and adjacent pancreatic islets to gain a better understanding of these diseases. Methods: We employed immunohistochemistry, Western Blot, real-time polymerase chain reaction, and in situ hybridization to examine IgG expression in PC tissues and adjacent islets with and without cancer-associated diabetes. The IgG mRNA and IgG synthesizing–related enzymes were examined in PC cell lines. The IgG expression and secretion were downregulated with specific small interfering RNA and antibody to IgG followed by flow cytometry to assess its effect on apoptosis of cultured PC cells. Results: The expression of IgG was detected in pancreatic carcinoma and adjacent islets. Small interfering RNA and antibody treatments induced apoptosis in PC cell lines. In the carcinoma tissue, the levels of IgG expression varied depending on the stages of the cancers with more malignant cancers expressing more IgG ( P < 0.05). The IgG levels in cancer cells were also increased when the patients had diabetes or hyperglycemia ( P < 0.05). In addition, the extent of IgG expression in the seemingly normal islet cells adjacent to the tumor varied in relation to the grade of cancer differentiation and distance to the cancer nests. Conclusions: (1) Immunoglobulin G was locally produced by PC cells and adjacent islet cells. (2) Immunoglobulin G may promote tumor growth by inhibiting cancer cell apoptosis. (3) Locally produced IgG might play a role in PC-associated diabetes. Abstract : Supplemental digital content is available in the text.